Magnetic flux quantum in a Superconducting concave/convex disk - Barba-ortega, J.; Joya, Miryam R.; Sardella, Edson [UNESP] (IOP Publishing, 2014)
The vortex state in a thin mesoscopic superconducting disk with a concave/convex surface is found theoretically. It is assumed that the outer edge of the sample is in contact with a metallic material. This configuration decreases the Bean-Livingston surface barrier energy, that is, it allows the vortex entry into the sample at lower magnetic field. In this work, we solve numerically the Ginzburg Landau equations with the metal/superconducting boundary condition using the link variable method in polar coordinates. It is shown that for a determined value for the deGennes parameter the superconductor becomes a type I superconductor and the irregular surface allows the vortex giant formation. The value of the thermodynamical properties decreases with this boundary condition and kind of surface.